Eksistensi Budaya Lempar Selendang Muli Mekhanai pada Masyarakat Lampung Pesisir Desa Sukajaya Punduh Kecamatan Marga Punduh Lampung - Aulia, Jihan; Qistina, Selamah Rabia; Agustina, Nelly (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2023)
This research aims to document and analyze the implementation of the "lempar selendang" cultural tradition in Sukajaya Punduh Village, Lampung. The primary focus is to understand the existence, development, and values embedded in this tradition. This study employs a qualitative approach with data collection techniques through interviews with traditional figures, youth, and young women in Sukajaya Punduh Village. Direct observations are conducted during the "lempar selendang" event, and a documentation approach is used to gather historical information related to this tradition. The research findings indicate: 1) The implementation of the "lempar selendang" cultural tradition in Sukajaya Punduh Village demonstrates continuity and adaptation to changes over time. 2) Despite shifts in the music used, values such as togetherness, camaraderie, and the sustainability of traditions are maintained. 3) Positive impacts of this event involve the enhancement of social skills, happiness, and the introduction of culture to outsiders. The research recommends the necessity of preservation efforts involving informal education for younger generations. The role of information technology can be optimized to promote and preserve traditional values.